Implementation of a Flagship Program in Instilling Religious Values in Students: Case Study at MTs Muhammadiyah - Setiadi, Agung Heru; Ma'ruf, Rachmad Arif; Darmanto, Darmanto; Abdillah, Muhammad Hanif; Asy'arie, Bima Fandi (AL-ISHLAH: Jurnal Pendidikan, 2024)
One of the efforts of madrasas to improve the quality of education is through superior programs because this activity has an important role in improving the management of madrasas that are dynamic, innovative, and full of ideas in shaping the development of students’ character who have religious values. This research is (1) to determine the application of superior programs in instilling religious values in students. (2) describe the implications of instilling religious values in students. The focus of this research was carried out at MTs Muhammadiyah 1 Malang, East Java. This research is field research; the type used is a case study with a qualitative approach. Data collection techniques (observation, interviews, documentation) were carried out on 25 informants through “Focus Group Discussion” (FGD). First, the process of implementing this superior program is carried out through various religious activities, forming an implementation schedule; coaching activities through homeroom teachers; exemplary values; and evaluating rewards/punishments as well as coordinating the institution with the homeroom teacher. This program aims to foster an Islamic environment, develop religious character, and integrate Islamic values into students’ daily lives. Second, the implications of this superior program can strengthen character, such as worship habits; provide guidance and motivation to students; strengthening morality, honesty, justice; building cooperation, mutual respect; build discipline, responsibility, and get closer to Allah SWT. Therefore, schools must continue to consider the long term so that the contribution of implementing superior programs in creating students’ religious values can be increased more effectively.